2007
DOI: 10.1084/jem20412oia28
|View full text |Cite
|
Sign up to set email alerts
|

Site-1 protease is essential for endochondral bone formation in mice

Abstract: Abbreviations used in this paper: Agc1, aggrecan; ATF6, activating transcription factor 6; BiP, immunoglobulin heavy chain binding protein; BSP, bone sialoprotein; Col I, type I collagen; CREBH, cAMP-responsive element binding protein H; E, embryonic day; ERSS, ER stress signaling; IHC, immunohistochemistry; Ihh, Indian hedgehog; MMP, matrix metalloproteinase; OASIS, old astrocyte specifi cally induced substance; PECAM-1, platelet/endothelial cell adhesion molecule 1; Ptc-1, Patched-1; PTHrP, parathyroid hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…However, if such high pressures would arise, they would likely be detrimental to the cell. Indeed, S1Pcko mice show severe intracellular changes, exemplified by severely disrupted endoplasmic reticulum and a pathological fat-metabolism (Patra et al 2007). However, causality remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…However, if such high pressures would arise, they would likely be detrimental to the cell. Indeed, S1Pcko mice show severe intracellular changes, exemplified by severely disrupted endoplasmic reticulum and a pathological fat-metabolism (Patra et al 2007). However, causality remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Mbtps1-floxed mice were obtained from Dr. Jay Horton, Southwest Medical School and Dr. Linda Sandell, Washington University (18,19); Dmp1-cre mice were obtained from Dr. Lynda Bonewald, University of Missouri-Kansas City (15). Males (Mbtps1(flx/ϩ):Dmp1(cre/ ϩ)) were crossed with females (Mbtps1(flx/flx)) to obtain Mbtps1 cKO mice (Mbtps1(flx/flx):Dmp1(cre/ϩ)) offspring; this strategy deletes exon 2 of the Mbtps1 gene and should be effective in ablating expression of all expressed forms containing the catalytic site (18).…”
Section: Methodsmentioning
confidence: 99%
“…S6) at E16.5. Our previous studies had demonstrated that S1P ablation in the chondrocyte lineage resulted in intracellular Col II entrapment with abnormal cartilage that impeded endochondral bone development (Patra et al, 2014a(Patra et al, , 2007. However, S1P-ablation in the Osx lineage results in cartilage matrix very similar to WT.…”
Section: S1p Ablation In the Osx Lineage Delays Endochondral Bone Devmentioning
confidence: 99%
“…S1P ablation in osteochondroprogenitors in mice (S1P cko ; via Col2-Cre) results in chondrodysplasia (Patra et al, 2014b(Patra et al, , 2007. These mice show abnormal cartilage development with type IIB procollagen ( pro-Col IIB) entrapment in the chondrocyte ER and a drastic reduction in type II collagen (Col II) protein in the cartilage.…”
Section: Introductionmentioning
confidence: 99%